1997
DOI: 10.1007/pl00007002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought on Graminicide Phytotoxicity in Wild Oat (Avena fatua) Grown under Different Temperature and Humidity Conditions

Abstract: Controlled environmental experiments were carried out to determine the phytotoxicity of several graminicides on wild oat (Avena futua L.) as influenced by combination of drought and temperature stress or drought and low relative humidity. Compared with unstressed conditions (20/15°C plus adequate soil moisture), imazamethabenz phytotoxicity to wild oat was reduced significantly when plants were exposed to a combination of drought and high temperature (30/20°C) stress. Imazamethabenz phytotoxicity was reduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
2
6
0
4
Order By: Relevance
“…Proline is an important osmoticum in higher plants. The benefit of the accumulation of proline has been proposed as a compatiable osmotic solute (Handa et al, 1986), as a protein-stabilizing or solubilizing factor under limited cell water conditions (Blackman, 1992) and as a source of reduced nitrogen and carbon (Xie et al, 1997). Previous work (Peter & Masumin, 1994) indicated that organic acid and amine compounds, except proline, were minor contributors to osmotic adjustment.…”
Section: Inorganic Cationsmentioning
confidence: 96%
“…Proline is an important osmoticum in higher plants. The benefit of the accumulation of proline has been proposed as a compatiable osmotic solute (Handa et al, 1986), as a protein-stabilizing or solubilizing factor under limited cell water conditions (Blackman, 1992) and as a source of reduced nitrogen and carbon (Xie et al, 1997). Previous work (Peter & Masumin, 1994) indicated that organic acid and amine compounds, except proline, were minor contributors to osmotic adjustment.…”
Section: Inorganic Cationsmentioning
confidence: 96%
“…A hipótese de que temperatura do ar elevada favorece a eficácia de herbicidas inibidores da ACCase no controle de plantas daninhas tem limites (Xie et al, 1997;Hatterman-Valenti et al, 2006;Andrews et al, 2007;Cieslik, 2012). Em espécies vegetais de clima frio, como Avena spp., o efeito da temperatura do ar sobre a atividade de clodinafop foi quadrático.…”
Section: Temperatura Do Arunclassified
“…Na mesma espécie vegetal, a toxicidade de fenoxaprop e diclofop às plantas foi reduzida quando em temperatura do ar elevada (30/ 20 o C dia/noite). O efeito adverso da alta temperatura do ar no controle das plantas de aveia com fenoxaprop foi compensado, em parte, pela elevação da dose do produto (Xie et al, 1997). A menor atividade desse herbicida pode ser atribuída à reduzida retenção de calda (Xie et al, 1995), ao aumento na desintoxicação do produto (Xie et al, 1996) e, possivelmente, à intensa evaporação das gotas aspergidas sob elevada temperatura do ar.…”
Section: Temperatura Do Arunclassified
See 2 more Smart Citations